Pengaruh Penggunaan Modul Berorientasi Pendekatan Saintifik dalam Model Problem Based Learning (PBL) Terhadap Pembelajaran Fisika Kelas XI di SMAN 1 Bukittinggi - Novita Novita; Hidayati Hidayati; Masril Masril (Universitas Negeri Padang, 2018)
Differences in Learning Outcomes Learners Using Scientific Approach-Oriented Modules in Physics Model Class XI in SMA Negeri 1 Bukittinggi. This research is based on the unfinished achievement of Physics competence of students in SMA caused by various factors such as the existence of teaching materials applied by educators. Teaching materials is one way that is considered effective to remind students of Physics learning outcomes. Module is one form of teaching materials. This study aims to determine the difference in the use of scientifically oriented approach module in the problem-based learning model of learning toward the achievement of physics competence of students of class XI SMAN 1 Bukittinggi. The type of research conducted is a quasi experiment with Randomized Control Group Design Only design. The study population is all students of class XI IPA SMAN 1 Bukittinggi registered in Lesson Year 2016/2017. Sampling is done by Purposive Sampling technique. Research data include competence from three aspects, namely attitude aspect obtained through observation sheet, knowledge aspect obtained through result of learning test, and skill aspect obtained through performance sheet. Physical material involved in this study deals with mechanical waves. To know the difference of using module is done with t test statistic, continued with simple linear regression analysis and product moment correlation test to research variables. Based on data analysis, the students' physics competence in attitude, knowledge, and skill in the experimental class were 81,2, 79, and 80,81 higher than the control classes 77,13, 75 and 78,33. The result of t test is that there is a significant difference between the achievement of Physics competence of learners using the Scientific Approach Oriented Module with the not. From the result of data analysis with significance level 0,05, the effect of Science-oriented Approach Module on knowledge, and skill are 60,84% and 23,04%.